Clinical Risk Factors For Kidney Tubule Biomarker Abnormalities Among Hypertensive Adults With Reduced eGFR in the SPRINT Trial. (12th September 2022) - Ikeme, Jesse C; Katz, Ronit; Muiru, Anthony N; Estrella, Michelle M; Scherzer, Rebecca; Garimella, Pranav S; Hallan, Stein I; Peralta, Carmen A; Ix, Joachim H; Shlipak, Michael G
Abstract: BACKGROUND: Urine biomarkers of kidney tubule health may distinguish aspects of kidney damage that cannot be captured by current glomerular measures. Associations of clinical risk factors with specific kidney tubule biomarkers have not been evaluated in detail. METHODS: We performed a cross-sectional study in the Systolic Blood Pressure Intervention Trial among 2, 436 participants with a baseline estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 . Associations between demographic and clinical characteristics with urine biomarkers of kidney tubule health were evaluated using simultaneous multivariable linear regression of selected variables. RESULTS: Each standard deviation higher age (9 years) was associated with 13% higher levels of chitinase-3-like protein-1 (YKL-40), indicating higher levels of tubulointerstitial inflammation and repair. Men had 31% higher levels of alpha-1 microglobulin and 16% higher levels of beta-2 microglobulin, reflecting worse tubule resorptive function. Black race was associated with significantly higher levels of neutrophil gelatinase-associated lipocalin (12%) and lower kidney injury molecule-1 (26%) and uromodulin (22%). Each standard deviation (SD) higher systolic blood pressure (SBP) (16 mmHg) was associated with 10% higher beta-2 microglobulin and 10% higher alpha-1 microglobulin, reflecting lower tubule resorptive function. CONCLUSIONS: Clinical and demographic characteristics, such as race, sex, and elevated SBP, are associated with unique profiles of tubular damage, which could reflect under-recognized patterns of kidney tubule disease among persons with decreased eGFR. Graphical Abstract: